Injection of vitamin A at insemination and reproductive performance in gilts - Schoneweis, D.; Nelson, M.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This experiment tested the hypothesis that an injection of vitamin A on the day of first detected estrus would improve reproductive performance of gilts. Gilts (432) were assigned to either receive vitamin A (1,000,000 IV) or placebo injected intramuscularly on the first day of estrus. No differences in farrowing rate, number of pigs farrowed per litter, or birth weight of pigs were detected. Possibly, gilts do not respond to vitamin A with improved fecundity. Other workers have reported an improvement in litter size for sows. Alternatively, treatment with vitamin A may need to precede estrus to improve litter size or multiple injections may be required. Experiments showing benefits for sows have treated them at weaning and, therefore, a few days before estrus.
Keywords: Swine; Gilts; Vitamin A; Litter size